Posterior Lateral Meniscal Root Tears Increase Strain on the Reconstructed Anterior Cruciate Ligament: A Cadaveric Study - William Uffmann, M.D; Neal ElAttrache, M.D; Trevor Nelson, B.S; Sam A. Eberlein, B.S; Juntian Wang, M.D; Daniel R. Howard, M.D; Melodie F. Metzger, M.D (Elsevier, 2021)
Purpose: To quantify the amount of strain across an anterior cruciate ligament reconstruction (ACLR) before and after a lateral meniscus (LM) posterior root complex tear and determine whether a meniscal root repair effectively protects the ACLR against excessive strain. Methods: Fresh-frozen cadaveric knees were tested with an 88-N anterior drawer force and an internal and external torque of 5-Nm applied at 0°, 15°, 30°, 60°, and 90° of flexion. A simulated pivot shift was also applied at 0, 15, and 30° of flexion. Rotation and translation of the tibia, and strain across the ACL graft were recorded. Testing was repeated for the following four conditions: ACL-intact, ACLR with intact LM, ACLR with LM posterior root complex tear, and ACLR with root repair. Results: The kinematic data from 12 fresh frozen cadaveric knees underwent analysis. Only 11 specimens had usable strain data. Sectioning the meniscofemoral ligaments and the LM posterior root increased rotational and translational laxity at 30° of knee flexion. ACLR graft strain significantly increased when an anterior load and internal torque were applied. Repair of the LM posterior root reduced strain when the knee was internally rotated but was unable to normalize strain when an anterior force was applied. Conclusions: This cadaveric biomechanical study suggests injury to the LM posterior root complex increases rotational and anterior laxity of the knee and places increased strain across reconstructed ACL grafts. Subsequent root repair did not result in a statistically significant reduction in strain. Clinical Relevance: This study provides quantitative data on the implications of a LM posterior root injury in the setting of an ACL reconstruction to help guide clinical decision-making.